Empowering rural women through backyard poultry farming: Adoption of Haringhata Black in tribal district of West Bengal - GUPTA, MOUMITA DEY; MONDAL, SHYAMAL KUMAR; BASU, DEBABRATA; PAN, SUBHRANSU; MITRA, KALYAN (The Indian Journal of Animal Sciences, 2022)
Rural women play a vital role in agricultural and allied sectors development but often lack the empowerment and recognition. The present paper aims to present a simple but effective empowerment strategy for rural women with backyard poultry farming. A sample size of 150 self-help groups (SHG) women members who were rearing backyard poultry belonging to ten different villages of Bankura; which were selected purposively based on highest populated SC/ ST villages of the district. The project was funded by District Magistrate office, ATMA, Bankura which included one demonstration unit at KVK Campus and other with SHGs at 10 villages. Skill development training programme were conducted to the selected SHG women on the various backyard poultry technologies /practices identified in the scheme and inputs like day-old chicks, feeds and vaccines were distributed to them. Follow-up visits for evaluation and monitoring were regularly conducted for offering technical advice. Three fourths (75%) of the beneficiaries expressed that they were economically empowered and their savings habit had improved after participation in the scheme. Majority (90%) observed that obtained additional income through this project on following the various low cost management technologies. Regression analysis revealed that position and involvement in family affairs has got positive and significant value while independent decision making authority and availability of low input birds are significantly associated with the empowerment of rural women in the sample area. Overall, the scheme created economical, social, psychological and technological impact among the poultry women facilitating empowerment of women in rural areas.